Beispiel Nr: 16
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ x^3-4x^2+3x =0\\ \\ \textbf{Rechnung:} \\ x( x^2-4x+3)=0 \Rightarrow x=0 \quad \vee \quad x^2-4x+3=0\\ \\ 1x^{2}-4x+3 =0 \\ x_{1/2}=\displaystyle\frac{+4 \pm\sqrt{\left(-4\right)^{2}-4\cdot 1 \cdot 3}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{+4 \pm\sqrt{4}}{2} \\ x_{1/2}=\displaystyle \frac{4 \pm2}{2} \\ x_{1}=\displaystyle \frac{4 +2}{2} \qquad x_{2}=\displaystyle \frac{4 -2}{2} \\ x_{1}=3 \qquad x_{2}=1 \\ \underline{x_1=0; \quad1\text{-fache Nullstelle}} \\\underline{x_2=1; \quad1\text{-fache Nullstelle}} \\\underline{x_3=3; \quad1\text{-fache Nullstelle}} \\$